PENGARUH BRAND IMAGE DAN PROMOTION TERHADAP KEPUTUSAN MAHASISWA BARU MEMILIH UNIVERSITAS DEHASEN SEBAGAI TEMPAT KULIAH (STUDI PADA MAHASISWA BARU ANGKATAN 2023) - Hanifun, Iqbal; Onsardi, Onsardi (UM. Bengkulu, 2024)
This study aims to determine the influence of Brand Image and Promotion variables on the decision to choose. This research uses a quantitative method. The population in this study is all students of Dehasen University of the 2023 intake with a total population of 2056, and 334 respondents were selected as samples. The sampling technique used was purposive sampling. Data collection was carried out using questionnaires. The results of this study indicate that: (1) There is a positive influence of the Brand Image variable on the Decision to Choose. Based on the results of partial tests, a t-value of 5.983 and a regression coefficient of 0.575 with significance of 0.000 were obtained. (2) There is a positive influence of the Promotion variable on the Decision to Choose. Based on the results of partial tests, a t-value of 2.260 and a regression coefficient of 0.210 with significance of 0.024 were obtained. (3) Brand Image and Promotion have a positive influence on the Decision to Choose. This is evidenced by the test result of an F-value of 29.069 compared to the F-table value of 3.870 and a significance value (0.000 <0.050). Keywords : Brand Image, Promotion, Decision to Choose